Lenz and Manquilef: the creation of an ethnic subject - Ruiz Figueroa, Fernando (Boletín de Filología, 2020)
Through the discourse analysis of the paratexts present in Manuel Manquilef’s book: “Comentarios del Pueblo Araucano” (1911), this study demonstrates how an ideology that relegates Mapuche language and culture to Chilean folklore is expressed. Rodolfo Lenz, as editor of this text, presents himself as the linguistic and editor the leads the reading of Manquilef’s central text, presenting it as the useful raw material for form Chilean national identity.